Contribution of Posidonia oceanica meadows in the context of climate change mitigation in the Mediterranean Sea. (March 2021) - Pergent-Martini, Christine; Pergent, Gérard; Monnier, Briac; Boudouresque, Charles-François; Mori, Christophe; Valette-Sansevin, Audrey
Abstract: Coastal marine vegetation has been recently highlighted for its highly efficient carbon storage capacity. Among the sixty-four species of seagrass, Posidonia oceanica, a Mediterranean endemic species, appears to be the most effective in carbon fixation and storage. Based on new data from the study of one of the largest P. oceanica meadows in the Mediterranean Sea (100 km of coastline, 20 425 ha), and a synthesis of available data from the whole of the Mediterranean basin, the aim of this work is to evaluate the amount of carbon fixed each year by P. oceanica and sequestered in the matte, in relation with the mitigation of the impact of climate change (carbon sink). The mean total carbon fixation (blades, sheaths and rhizomes) per year varies between 33.5 and 426.6 g C.m −2 and the mean carbon sequestration (long-term sink in the matte), corresponding to the sheath and rhizome tissues, varies between 7.7 and 84.4 g C.m −2, with a clear decreasing trend according to depth because of the meadow density decrease. The synthesis of a hundred measurements made throughout the Mediterranean Sea and at depths between 0.5 and 32.0 m provides a basis for estimating the average annual carbon fixation and sequestration rate throughout the Mediterranean basin. The fixation of the blades is estimated at 1 024 t C.ha −1 .yr −1, that of the sheaths at 220 t C ha −1 .yr −1 and that of the rhizomes at 58 t C ha −1 .yr −1 ; i.e. a total fixation rate of 1 302 t C ha −1 .yr −1 and sequestration rate (dead sheaths and rhizomes) of 278 t C ha −1 .yr −1 . This annual carbon fixation represents only 0.61% on average of CO2 emissions/releases for all Mediterranean countries but in the large Mediterranean islands this fixation is on average 3.1% and can reach almost 14.4% for Corsica. Moreover, the major advantage of the P. oceanica meadow lies in its capacity to store carbon from annual carbon sequestration for centuries to millennia and can be compared to several terrestrial ecosystems considered to be efficient in carbon storage (peatlands). Highlights: First assessment of carbon fixation and sequestration by Mediterranean seagrass. 5 681 206 tons of CO2 emissions, are fixed annually by Posidonia oceanica . 21% of this carbon is sequestered, annually, by the Posidonia oceanica soil (matte). For Mediterranean islands, carbon fixation can reach up to 14.5% of carbon emissions.